The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.5539/mas.v9n4p344
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Strategic Alternatives in Agribusiness

Abstract: The article deals with the problems of strategic management using the methods of multidimensional statistical analysis. In agribusiness, the gap may occur in the use of modern management tools; therefore, the strategies used by agricultural producers are not always formalized. To study the latent strategies as the models of economic behavior, the technique of identification of strategic alternatives was developed based on the system use of the cluster analysis, trend analysis, and the method of canonical corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The service of such information support should include structures that provide advice to commodity producers [22,23]. Thus, the system of information and consulting services should contribute to the development of the strategic management process, which is in the same time leads to an increase in the competitiveness of agricultural enterprises.…”
Section: Results Of the Studymentioning
confidence: 99%
“…The service of such information support should include structures that provide advice to commodity producers [22,23]. Thus, the system of information and consulting services should contribute to the development of the strategic management process, which is in the same time leads to an increase in the competitiveness of agricultural enterprises.…”
Section: Results Of the Studymentioning
confidence: 99%
“…Analysis of works of modern scientists on the problem of development of agribusiness showed that most of research is devoted to substantiation of expedience and necessity for development of agribusiness; among them are the works of (Garthwaite et al, 2015), (He, 2015), (Jacknowitz et al, 2015), (Maitra &Rao, 2015), (Mazaeva and Rogachev, 2012), and (Bannikova et al, 2015). Also, a large number of works are oriented at allocation of national peculiarities of development of agribusiness and solving the problems of particular socio-economic systems, related to provision of food security: (Grouiez, 2012), (Bernardes, 2015), and (Medernach & Burnod, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…It is tailored toward the establishment of the business. According to (Bannikova, Baydakov, & Vaytsekhovskaya, 2015), a stable strategy is intended for stable companies to develop their business. The company believes that it has the potential to be successful and involves less risk.…”
Section: Reactive and Cost Leadership Strategy For Stabilitymentioning
confidence: 99%